Quantifying the burden of opioid medication errors in adult oncology and palliative care settings: A systematic review. (June 2016) - Heneka, Nicole; Shaw, Tim; Rowett, Debra; Phillips, Jane L
Background: Opioids are the primary pharmacological treatment for cancer pain and, in the palliative care setting, are routinely used to manage symptoms at the end of life. Opioids are one of the most frequently reported drug classes in medication errors causing patient harm. Despite their widespread use, little is known about the incidence and impact of opioid medication errors in oncology and palliative care settings. Aim: To determine the incidence, types and impact of reported opioid medication errors in adult oncology and palliative care patient settings. Design: A systematic review. Data sources: Five electronic databases and the grey literature were searched from 1980 to August 2014. Empirical studies published in English, reporting data on opioid medication error incidence, types or patient impact, within adult oncology and/or palliative care services, were included. Popay's narrative synthesis approach was used to analyse data. Results: Five empirical studies were included in this review. Opioid error incidence rate was difficult to ascertain as each study focussed on a single narrow area of error. The predominant error type related to deviation from opioid prescribing guidelines, such as incorrect dosing intervals. None of the included studies reported the degree of patient harm resulting from opioid errors. Conclusion: This review has highlighted the paucity of the literature examining opioid error incidence, types and patient impact in adult oncology and palliative care settings. Defining, identifying and quantifying error reporting practices for these populations should be an essential component of future oncology and palliative care quality and safety initiatives.